Aspectos de la gramatización antigua de la lengua vasca - Aurélie Arcocha-Scarcia; Joseba Andoni Lakarra (Lengas)
Following the state of affairs (§1.1) in studies on the LVP, we showcase two complementary points of view for their correct understanding, i.e., their “publication as a book” and the role played therein by Morpain and Lehet (§1.3) in Bordeaux, the humanist and reformist focus following the creation of the College of Guienne (§1.2) and in 1.4. we provide some notes on the initial stages of the Bordeaux printing press. In 1.5. We focus on the similarities of Etxepare with humanists and the Renaissance prior to Du Bellay like in Tory and Dolet and in §1.6 we present a lexical examination of the Epistola Dedicatoria, Contrapas and Sautrela that takes us in that same direction. In §1.7 and §1.8 we underscore the parallel between the "Debile principium" and Rabelais and the remembering the Basque fragments of Rabelais. In §2 we show the context of the book’s repression and the religious wars during which Leizarraga’s work (§2.1) emerged, emphasising the deep meaning that La Rochelle and Haultin contributed to L’s translation work (§2.2), and we analyse the problem of his original or “hypotext” (§2.3), an inescapable task in order to understand its praxis and objectives; in §2.4. We present a new approach in the search for the translated model from the analysis of loans words without same linguistic roots and in 2.5 we remember that grammarization does not imply standardised unification of the language. The sibilants In §2.6 and §2.7, certain Leizarraga graphic options are examined, related to the doctrines of French Protestant grammarians and printers: and biunivocity in sibilants with distinction of fricative and affricate sounds.. In §3 we address aspects of the grammatization of RS, contrasting it with Garibay and other old testimonies: in 3.1 we analyse the size of RS and the "direction" of the translation (Basque/Spanish); in 3.2 we examine certain very marked spellings of RS within the Basque text tradition ( and apical affricate sibilant), related more to the French than the Hispanic tradition; in 3.3 we demonstrate that Mares and not Porralis was the true publisher of the RS and in 3.4 that, in reality, this work was above all a teaching / learning instrument for languages (partic. Basque), a function demonstrated by its singular structure with numbers over each word (§3.5) and in §3.6 we include a coda about the origins of RS incuding the role of Mares is included. In §4 we include the principal conclusions, among which that publications in the vernacular language needed the establishment of linguistic tools, the development of grammatization and a cultural context that permitted the “enlightening” of the language; for that reason, both the LVP and the NT and the RS were born within a continuum, not ex-nihilo or on an island, which makes it essential to reread these works in relation to the printing workshops, scrutinising their ideological surroundings in the context of the extension of new ideas, in an interconnected geopolitical space which experienced major jumps and evolutions in this period. The cited bibliography is included in §5.